UTILITARIANISME DAN PERANNYA DALAM PROSES PENYUSUNAN RENCANA ANGGARAN PENDAPATAN DAN BELANJA DAERAH (RAPBD) - Perdana, Syafaat Anugrah; Syah, Muh Aslam (Institut Agama Islam Negeri Ternate, 2023)
In the science of law, it is known as a school or school that is adhered to by everyone where there tends to be a dogmatic nature in that school. One of the schools that exist is the school of utilitarianism pioneered by Jeremy Bentham which states that the purpose of law is to provide the greatest happiness to the greatest number. One of the legal policies referred to is the RAPBD which is stipulated through a Regional Regulation whose drafting authority is given to the DPRD together with the Regional Government. Where in the process of drafting the RAPBD as a legal product it must be under the substance of the legal ideals namely certainty, justice, and expediency. So it needs to be investigated academically regarding the role of utilitarianism in the drafting process of the RAPBD. This research is normative research that uses a literature approach where the source of data comes from legislation and legal theories. This research results in the conclusion that the concept of utilitarianism has an important point in the process of preparing the RAPBD because the ultimate goal of the budget is to provide welfare value to society in general.Keywords: APBD; Utilitarianism; RAPBD.